2014
DOI: 10.1002/pssa.201431618
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced growth of aluminum nanowires with a range of cross-sections

Abstract: The use of aluminum (Al) as a plasmonic building block has drawn increasing attention of late, due to its natural abundance, and extended tunability into the ultraviolet range. However, a controllable way to grow Al nanowires (NWs) in a bottom-up manner has not been reported. Here a facile, stress-induced growth process for Al nanowires, influenced by the concentration of applied hydrofluoric acid, is reported. Physical characterizations show the nanowires to be polycrystalline fcc Al with ultrasmooth surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
10
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, it is an abundant, sustainable material with the potential to transition laboratorybased research into practical applications and commercial products. Much of the current and growing interest in Aluminum plasmonics is due to the wavelength range of the plasmon resonances obtainable with simple geometries.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, it is an abundant, sustainable material with the potential to transition laboratorybased research into practical applications and commercial products. Much of the current and growing interest in Aluminum plasmonics is due to the wavelength range of the plasmon resonances obtainable with simple geometries.…”
mentioning
confidence: 99%
“…Additionally, the Au nanowires have been exhibited to function as bio-and chemical-sensors (Zhang et al 2009;Moon et al 2014). The study has reported surface plasmon propagation along a single metal nanowire (Ditlbacher et al 2005;Ye et al 2015). Micro/nanoscale systems using micro/nanowires are assembled by organizing and welding wires with each other (Whang et al 2003;Garnett et al 2012;Tohmyoh and Fujimori 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though several metallic elements, such as Ag, Cu, Au, and Ni, are useful to fabricate micro/nanowires, it is difficult to fabricate the Al micro/nanowires because of the high reactivity of Al with acids and bases. The aforementioned chemical growth methods that can be used to fabricate metallic micro/nanowires are restricted to the fabrication of noble metals, as observed by Ye et al (2015). In the previous few years, attempts have been made to fabricate free-standing Al micro/nanowires by oblique angle deposition (Li et al 2008), stress-induced migration (Chen et al 2012;Ye et al 2015), and template-based assembly (Nesbitt et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal and semiconductor NWs have enabled new applications in nanotechnology ranging from single-NW logic gates to plasmonic waveguides for nanophotonics, nanolasers, , and highly selective catalysts . Plasmonic waveguides based on metallic NWs have been investigated extensively for their use in nanophotonic integrated circuits. , Aluminum (Al) NWs fabricated by template approaches are suitable for plasmonic waveguides, but their relatively complex preparation protocol has limited this approach, compared to the more straightforward chemical synthesis of noble metal NWs. Recently, chemical synthesis of Al NCs with controlled sizes, shapes, and varied surface chemistries has made Al a practical alternative to noble metal nanoparticles for plasmonics. By chemically controlling the size and shape of Al NCs, the collective electronic oscillations of the nanoparticle (its localized surface plasmons) can be spectrally tuned from the ultraviolet (UV) through the visible and into the infrared (IR) regions of the electromagnetic spectrum. Through chemical modification of their surface oxide, Al NCs have been tailored for applications ranging from molecular sensing to plasmon-enhanced photocatalysis. For example, Al nanocubes were used to fabricate highly efficient bimetallic Pd–Al nanoparticle catalysts with Pd selectively grown at the cube vertices . Despite these advances, the high-yield synthesis of highly anisotropic nanocrystal morphologies, such as nanorods and NWs, has remained elusive. Relatively large single-crystalline Al nanorods were synthesized by pyrolysis of triisobutyl aluminum (TIBA) in trioctylamine at 250 °C, but only constituted ∼15% of the sample .…”
mentioning
confidence: 99%